Comparison of high-flow nasal cannula and noninvasive positive pressure ventilation in children with acute bronchiolitis - Anil Sachdev; Rohit Vohra; Neeraj Gupta; Dhiren Gupta; Suresh Gupta (Wolters Kluwer Medknow Publications, 2020)
Objective: In recent years, there has been an increase in the use of noninvasive positive pressure ventilation (NIPPV) and high-flow nasal cannula (HFNC) in children with increased work of breathing due to acute bronchiolitis. However, there are only limited studies comparing the efficacy of these two interventions. This study was done to compare efficacy and patients' comfort while receiving HFNC and NIPPV for acute bronchiolitis. Materials and Methods: Children admitted with the first episode of acute bronchiolitis with respiratory distress (modified Wood's Clinical Asthma Score >3) were randomized to receive NIPPV and HFNC. FiO2was titrated to achieve a SpO2of ≥94%. If the child was agitated and had a COMFORT B score of ≥17, dexmedetomidine infusion was started. The protocol lasted for at least 24 h or till the respiratory support was required as decided by the treating physician. Outcome parameters measured were failure of intervention and patient comfort (using COMFORT B scores). Social science system version SPSS 17.0 was used for statistical testing.P < 0.05 was taken to indicate a significant difference for all statistical tests. Results: Twenty-five cases were enrolled in each study group. Failure of therapy was noted in 11 (44%) patients in the HFNC group and 6 (24%) in the NIPPV group (P = 0.18). COMFORT B score was significantly better in the HFNC group as compared to the NIPPV group (NIPPV12 vs. HFNC 8;P < 0.001). A number of cases requiring sedation and duration of sedation (dexmedetomidine) were more in the NIPPV group as compared to the HFNC group (22 vs. 10, P = 0.02, and 31.2 vs. 20.6 h, P = 0.04). Conclusion: This study suggests that possibly HFNC and NIPPV are equally efficient in the treatment of moderate-to-severe bronchiolitis. HFNC is more comfortable for bronchiolitis patients in comparison to NIPPV.